(untitled) (RevistAleph, 2018)
Este artigo é uma síntese das reflexões de uma monografia de um curso voltado à formação de professores. Visibilidade é dada a uma experiência autoformativa do autor que teve na expressão do “devir” de sua condição existencial o seu lugar primordial. A narrativa (auto)biográfica aliada à valorização da arte em sua vida despertou memórias que suscitaram problematizações acerca de sua escolarização. Para os fins desse artigo, é dado ênfase às reflexões que emergiram desse processo questionando as limitações de determinado paradigma escolar expondo assim um de seus maiores entraves: a indissociação entre razão e emoção, mente e corpo. São aqui discorridas, ao final, as contribuições da arte e das ideias da desescolarização para pensar a escola. This article is a synthesis of the reflections of a monograph of a course focused on teacher education. Visibility is given to a self-formative experience of the author who had in the expression of the "becoming" of his existential condition his primordial place. The (auto)biographical narrative allied to the valorization of art in the author’s life sparked memories that gave rise to problematizations about his schooling. For the purposes of this article, emphasis is placed on the reflections that emerged from this process by questioning the limitations of a particular school paradigm, thus exposing one of its greatest obstacles: the indissociation between reason and emotion, mind and body. Finally, the contributions of the art and ideas of non-schooling to think the school are discussed here.